Pentingnya Guru Pak Dalam Menanamkan Nilai-Nilai Kristiani Tehadap Anak-Anak Remaja Di SMP Negeri 25 Pontianak Terkhusunya Kelas VII Dan VIII - Salom Gabriel Abiaser Dael (Institut Teknologi dan Bisnis Semarang, 2024)
The role of PAK teachers is very imporatant, especially in instilling Christian values in student and shaping the personality of student in accordance with Christian Values. Student at SMP NEGERI 25 PONTIANAK in terms of declined dud to a lack of spiritual guidance for them.With things like this without thinking of a solution for the future of students. basically parents of students have good expectations for spiritual growth in the future of their children.however, there are no PAK teachers who have teh determination to carry this out, so thet the attitudes and characteristics of students at SMP NEGERI 25 PONTIANAK are decreasing day by day and are not in line with their parents’ expecatations because there are no pak teachers who reach out to them. the role of PAK teachers has not maximally instilled Chirstian values in students to be applied in the lives of students.